2020
DOI: 10.1002/elps.202000149
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized free‐flow electrophoresis: production, optimization, and application using 3D printing technology

Abstract: The increasing resolution of three‐dimensional (3D) printing offers simplified access to, and development of, microfluidic devices with complex 3D structures. Therefore, this technology is increasingly used for rapid prototyping in laboratories and industry. Microfluidic free flow electrophoresis (μFFE) is a versatile tool to separate and concentrate different samples (such as DNA, proteins, and cells) to different outlets in a time range measured in mere tens of seconds and offers great potential for use in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…The separation spiral was developed using design guidelines and the design equation articulated by Di Carlo [ 8 ] to facilitate focusing of 18 µm particles (or cells) at a flow rate of 1000 µL min −1 (see Equation (1)). Additionally, the height of the spiral channel was 200 µm, since prior experiments have demonstrated that this size can be reliably produced using the 3D printer [ 19 , 20 ]. …”
Section: Methodsmentioning
confidence: 99%
“…The separation spiral was developed using design guidelines and the design equation articulated by Di Carlo [ 8 ] to facilitate focusing of 18 µm particles (or cells) at a flow rate of 1000 µL min −1 (see Equation (1)). Additionally, the height of the spiral channel was 200 µm, since prior experiments have demonstrated that this size can be reliably produced using the 3D printer [ 19 , 20 ]. …”
Section: Methodsmentioning
confidence: 99%
“…3-D printing is an alternative way of generating even complex 3D-structures. Various printing approaches can be used, such as: stereolithography- SLA [ 91 ], inkjet (including multijet) [ 92 , 93 ] or fused deposition modeling (FDM) [ 94 , 95 ] techniques. Among these, stereolithography offers some specific advantages versus the other printing techniques, especially better resolution, tighter tolerances and better compatibility with the thermoset polymers [ 96 ].…”
Section: Design and Fabrication Of The Microfluidic Systemsmentioning
confidence: 99%
“…Certainly, additional techniques such as electrospinning can be used to develop films with oriented or un-oriented patterns to assure specific functions within the more complex devices, including advance separation and cell growth and manipulation under biomimetic conditions [ 93 , 100 ]. Interconnection of the individual units in microfluidic multi-organ-o-a-chip and the possibility of assuring crosstalk of these tissues from different chambers can be also assured by using 3D-printing [ 101 ].…”
Section: Design and Fabrication Of The Microfluidic Systemsmentioning
confidence: 99%
“…The microchannels were located at the bottom layer of the printing plane and in parallel to the printing direction. The printer resolution was 32 μm and a deviation of 10% in size was reported for features with sizes of 100 to 200 μm [38]. After printing, the devices were subjected to several postprocessing steps, as previously described (see Supplementary information for more details) [6,39].…”
Section: Design and Fabrication Of 3d-printed Microfluidic Devicesmentioning
confidence: 99%